Regulation of endoreduplication by protein phosphatase 2A in Arabidopsis thaliana leaves - Winter, Zsofia (My University, 2018)
Plants display an adaptive growth where the size of the plant can be influenced by the environment. For normal growth and development in Arabidopsis thaliana leaves the mitotic cell cycle is essential for cell proliferation and endoreduplication for cell expansion. Endoreduplication results in an increased number of sets of chromosomes in the nucleus, called polyploidy. Protein phosphatase 2A (PP2A) is a trimeric protein phosphatase, containing a structural subunit A, a regulatory subunit B and a catalytic C subunit. The PP2A-B’γ regulatory subunit is a negative regulator of plant defense and salicylic acid (SA) dependent transcriptional responses in the model plant A. thaliana. Salicylic acid is a key plant hormone in plant immunity against several of pathogens. A recent study suggested that SA signaling is needed to alter cell-cycle progression, and it is known to influence endoreduplication in Arabidopsis leaves. The regulation of endoreduplication and its physiological importance is still not well defined. In this study, flow cytometry analysis was used to determine the polyploidy levels of wild type, pp2a-b’ and mutants with altered SA levels. Immunoblot analysis was used to reveal if the changes of endoreduplication levels could be associated with differences in the abundance of the SA signaling protein NONEXPRESSER OF PATHOGENESIS RELATED GENES 1 (NPR1) between the mutants. My study revealed that endoreduplication is affected by photoperiod. Furthermore, analysis by flow cytometry revealed that pp2a-b’ mutants display enhanced polyploidy compared to wild type, indicating that PP2A-B’γ and its close homolog, PP2A–B’ζ, regulate endoreduplication. Immunoblot analysis of nuclear extracts revealed no connection between NPR1 protein abundance and endopolyploidy levels. The identification of PP2A as a regulator of endoreduplication reveals a previously unrecognized layer of regulation underlying the growth and productivity of plants.
Keywords: Arabidopsis thaliana, protein phosphatase 2A, endoreduplication, salicylic acid, cell cycle